Evaluation of Inclusive Education Practices in Sarva Siksha Abhiyan (SSA) Primary Schools - Mishra, Amitav; Kumar, Girijesh (JOURNAL OF INDIAN EDUCATION, 2009)
The study aimed to evaluate the influence of inclusive education practices on learning and teacher attitude towards children with special needs as well as to evaluate how children with special needs placed in regular schools have benefited. Twenty children with disabilities of two from each 10-randomly selected schools were chosen for case study. A critical evaluation was done on all possible related variables responsible for meeting unique needs of child with disabilities such as: dropout/ retention; provision of incentives including aids and appliances; individualised programme; curricular adaptation; academic achievement; attitude of teachers and peers; and resource support to school. It was observed that not only mild and moderate, but children with disabilities having any severity level were part of the primary schools. Significant gap between school age and chronological age; lower grade level inappropriate examination practices were observed. Retention of children with disabilities was found good with appropriate attendance. Half of the teacher’s attitude towards these children were nor favourable; however, positive peer acceptance was observed. The present article also mentions all possible practical suggestions and recommendations.